A Unified Framework for E-Learning Continuity: Integrating Task-Technology Fit, Unified Theory of Acceptance and Use of Technology, and External Facilitators - Ababneh, Hayel; Shrafat, Fayiz; Baqleh, Lubnal; Vasudevan, Asokan; Mohammad, Anber (International Review of Management and Marketing, 2026)
The study forms a combined theoretical model to review the predictors of the e-learning continuance intention in higher education. The synthesis of the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Task-Technology Fit (TTF) model with the Management Support, Computer Self-Efficacy, Perceived Trust, and Perceived Autonomy provides a complete picture of the system persistence. Data were gathered through an electronic questionnaire that was given to the faculty members in both the public and the private universities in Jordan following a deductive, quantitative approach. The analysis of 220 valid responses shows that the main cause of Task-Technology Fit is the characteristics of technology, which in turn leads to the continuance intention. Moreover, the performance expectancy and facilitating conditions became the prevailing UTAUT constructs, whereas computer self-efficacy turned out to be the most powerful exogenous variable. This research not only adds to the body of knowledge a multidimensional model that is unique but also offers university administrators and system developers strategic wisdom to improve e-learning sustainability.